The Effect of Preoperative Oral Carbohydrate or Oral Rehydration Solution on Postoperative Quality of Recovery: A Randomized, Controlled Clinical Trial - Asakura, Ayako; Mihara, Takahiro; Goto, Takahisa (PLOS ONE, 2015)
Background Numerous studies have demonstrated the beneficial effects of preoperative administration of oral carbohydrate (CHO) or oral rehydration solution (ORS). However, the effects of preoperative CHO or ORS on postoperative quality of recovery after anesthesia remain unclear. Consequently, the purpose of the current study was to evaluate the effect of preoperative CHO or ORS on patient recovery, using the Quality of Recovery 40 questionnaire (QoR-40). Methods This prospective, randomized, controlled clinical trial included American Society of Anesthesiologists (ASA) physical status 1 and 2 adult patients, who were scheduled to undergo a surgical procedure of body surface. Subjects were randomized to one of the three groups: 1) preoperative CHO group, 2) preoperative ORS group, and 3) control group. The primary outcome was the global QoR-40 administered 24 h after surgery. Intraoperative use of vasopressor, intraoperative body temperature changes, and postoperative nausea and vomiting (PONV) were also evaluated. Results We studied 134 subjects. The median [interquartile range (IQR)] global QoR-40 scores 24 h after the surgery were 187 [177–197], 186 [171–200], and 184 [171–198] for the CHO, ORS, and control groups, respectively (p = 0.916). No significant differences existed between the groups regarding intraoperative vasopressor use during the surgery (p = 0.475). Conclusions Results of the current study indicated that the preoperative administration of either CHO or ORS did not improve the quality of recovery in patients undergoing minimally invasive body surface surgery. Trial Registration www.umin.ac.jp UMIN000009388 https://upload.umin.ac.jp/cgi-open-bin/ctr/ctr.cgi?function=brows&action=brows&type=summary&recptno=R000011029&language=E